RAYA GREEN'S AMBITION IN IAN IQBAL RASHID'S HOW SHE MOVE MOVIE (2007) : A PSYCHOANALYTIC APPROACH - SULFIAN, RANDY (2011)
The study tries to explore the ambition of the major character. The objective of the study is to analyze the major character based on the structural elements of the movie and psychoanalytic perspective. The researcher applies the theory of psychoanalytic proposed by Sigmund Freud. The writer conducts the research by using qualitative method that uses the library research, while the data sources are literary data that are divided into two categories, primary and secondary data. The primary data are the movie subtitle How She Move itself and the secondary data include several references books of Psychoanalysis. The object of the research is the movie entitled How She Move directed by Ian Iqbal Rashid. The results of the study are as follows. Firstly, the structural elements of the present a unity. It appears in the beginning, the middle, and the end of the story. Secondly, the psychoanalytic analysis shows that the problem of major characters encounters and causes the conflict between id, ego, and superego. Then, it develops to become tension and influences Raya's mental condition. And, Raya uses defense mechanism to reduce the tension.